Optimalisasi Peran Kader Kesehatan dalam Mengontrol Tekanan Darah Pasien Hipertensi dengan Terapi Sentuh dan Akupresur di Masa Pandemi Covid-19. - Yuli Widyastuti; Cemy Nur Fitria; Heni Purwaningsih (Sejahtera: Jurnal Inspirasi Mengabdi Untuk Negeri, 2024)
Hypertension is one of the major non-communicable diseases that has become a primary health concern, especially during the Covid-19 pandemic. Effective blood pressure control is crucial to prevent severe complications. The role of health cadres in monitoring blood pressure at home has become increasingly important, particularly with the application of non-pharmacological methods such as foot touch therapy and acupressure. This study aims to optimize the role of health cadres in assisting hypertensive patients to control their blood pressure using these techniques. The methods used include cadre training, patient education, and evaluation of intervention effectiveness. The results show that implementing foot touch therapy and acupressure can significantly reduce blood pressure and improve patients' well-being. Optimizing the role of health cadres in community-based hypertension management is expected to enhance patients' quality of life, especially in a pandemic situation that limits access to healthcare facilities.